Technological Innovation in Islamic Finance : An Analysis of the Government's Role in Regulating and Supporting Islamic Fintech - Alfian Widiyanto; Saefudin Zuhri (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The rapid development of technology has significantly influenced various economic sectors, including finance. Digitalization has introduced opportunities to create more efficient, transparent, and inclusive financial services. Within Islamic finance, technological advancements address challenges such as limited access to Sharia-compliant financial services and complexities in applying Sharia principles practically. One notable innovation is Sharia-based financial technology (fintech), which combines Islamic values with modern technology to provide accessible, ethical, and sustainable financial solutions. This study explores the potential and challenges of Sharia fintech in Indonesia, a country with the largest Muslim population globally. Sharia fintech, including crowdfunding, peer-to-peer lending, and halal digital payment platforms, promotes financial inclusion while adhering to Islamic principles. However, its growth faces regulatory hurdles, consumer protection issues, and a lack of public literacy about Sharia-compliant financial products. The research highlights the role of the government and regulatory bodies such as the Financial Services Authority (OJK) in providing a supportive framework, including legal certainty, technological infrastructure, and public education initiatives. The findings emphasize that effective regulations and strategic government support are critical to fostering Sharia fintech as a pillar of the Islamic economy. With strengthened collaboration between stakeholders, Sharia fintech can contribute significantly to financial inclusion and sustainable economic development in Indonesia.